DEVELOPMENT OF NEW WORKFLOWS TO IMPROVE HISTORY MATCHING AND PREDICTION FOR NATURALLY FRACTURED CARBONATE RESERVOIRS - ABED ALJUBOORI, FAISAL AWAD (2020)
Carbonate reservoirs in the Middle East hold a significant proportion of the remaining conventional oil reserves, which most of them were classified as naturally fractured.